Spatial assessment of land use and land cover change impacts on groundwater recharge and groundwater level: A case study of the Hat Yai basin - Nantiya Indhanu; Tanit Chalermyanont; Tanan Chub-Uppakarn (Journal of Hydrology: Regional Studies)
Study region: Hat Yai Basin, Thailand. Study focus: This study aimed to assess the impacts of land use and land cover changes on groundwater recharge and groundwater levels—specifically, the effects of increasing built-up areas and urban expansion. The MOLUSCE (plug-in QGIS) software was used to analyze land use and land cover changes. The groundwater recharge estimation in this study was conducted using the WetSpass model, and the groundwater level was simulated using MODFLOW. New hydrological insights for the region: The findings indicate that the Hat Yai basin has experienced its highest increase in built-up areas and found a decrease in the average recharge rate for 2017 compared to 2007. Correspondingly, a simulation of groundwater levels indicates that the overall groundwater level has decreased. Spatially, the Hat Yai district, which exhibited the highest increase in built-up areas, experienced a decrease in groundwater levels. In contrast, the Khuan Niang district, which had the largest increase in perennial areas, demonstrated increased groundwater levels. The findings show that increasing built-up areas decreases the recharge rate, consequently lowering groundwater levels. The spatial assessment is proved to be more effective in illustrating positive and negative impacts than the basin's overall average. Such spatial assessment is valuable for water resource management planning and addressing localized water resource issues that may differ across various areas.